2019
DOI: 10.1186/s12933-019-0902-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in behaviors after diagnosis of type 2 diabetes and 10-year incidence of cardiovascular disease and mortality

Abstract: Background Large changes in health behaviors achieved through intensive lifestyle intervention programs improve cardiovascular disease (CVD) risk factors among adults with type 2 diabetes. However, such interventions are not widely available, and there is limited evidence as to whether changes in behaviors affect risk of CVD events. Methods Among 852 adults with screen-detected type 2 diabetes in the ADDITION - Cambridge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 40 publications
1
18
2
1
Order By: Relevance
“…Information on intention to lose weight is not available in the ADDITION study, but among Cambridge participants only (N = 867), we collected questionnaire data on health behaviours. We previously showed that reductions in alcohol use and total calorie intake were associated with the lower 10‐year hazard of CVD, 22 but participants who made these changes did not necessarily lose weight. We did not count deaths during the year after weight change was assessed to reduce the chance of confounding by unintentional weight loss.…”
Section: Discussionmentioning
confidence: 96%
“…Information on intention to lose weight is not available in the ADDITION study, but among Cambridge participants only (N = 867), we collected questionnaire data on health behaviours. We previously showed that reductions in alcohol use and total calorie intake were associated with the lower 10‐year hazard of CVD, 22 but participants who made these changes did not necessarily lose weight. We did not count deaths during the year after weight change was assessed to reduce the chance of confounding by unintentional weight loss.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies evaluating other lifestyle scores like the American Heart Association Life Simple 7, that includes 4 lifestyle behaviors (BMI, smoking, diet, physical activity) and 3 clinical risk factors (blood pressure, high cholesterol, and diabetes) have found important inverse associations with CVD and total-mortality in different cohorts [ 63 68 ]. In addition, reductions in alcohol intake and energy intake over 1 year in participants with diabetes diagnosis was association with lower hazard of CVD [ 69 ]. However, the effect of behavioral factors may be attenuated after the development of the clinical risk factors which are associated with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a reduction in the risk of type 2 diabetes was observed in women (peak reduction at the level of consumption of 31–37 g of alcohol per day) [ 42 ]. Having said that, it was observed that among the patients with diagnosed diabetes, limiting alcohol consumption by at least 2 units/week decreased a 10-year risk of CVD (HR: 0.56, 95% CI 0.36, 0.87) [ 43 ]. Alcohol consumption is also a well-known risk factor for hypertension [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%